Strategi Branding Donat Pinkan Mambo dalam Meningkatkan Minat Beli Konsumen melalui TikTok - Danny Christiawan; Rini Darmastuti; Deasy Carolina (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2026)
Digital transformation has reshaped the marketing landscape, establishing TikTok as a crucial platform for brand identity development through intensive digital narratives. This research aims to analyze the branding strategy of Donat Pinkan Mambo in increasing consumer purchase intention via TikTok. The method employed is qualitative descriptive with a Qualitative Content Analysis approach focusing on live streaming content and digital interactions. The results indicate that the integration of personal vulnerability narratives with TikTok’s interactive features successfully creates strong brand differentiation. The "Donat Air Mata" emotional narrative strategy is proven effective in converting audience empathy into actual purchase actions, while premium pricing is validated by the moral values of the communicator's life struggles. The study concludes that authenticity and emotional attachment are the primary keys to building MSME brand equity in today's digital ecosystem. The success of this model demonstrates that honest human dimensions can surpass the dominance of conventional visual aesthetics in securing sustainable consumer loyalty.